Disclosure of the six capitals in strategy, risk and performance sections: Evidence from South Africa - Amy C.R. Steenkamp; Warren Maroun; Nirupa Padia; Dusan Ecim (South African Journal of Business Management)
Purpose: This article assesses the integration of multi-capitals in the strategy, risk and performance disclosures in 240 integrated reports of 30 South African-listed companies between 2013 and 2020.